2011
DOI: 10.1098/rsbl.2011.0260
|View full text |Cite
|
Sign up to set email alerts
|

Are soils in urban ecosystems compacted? A citywide analysis

Abstract: Soil compaction adversely influences most terrestrial ecosystem services on which humans depend. This global problem, affecting over 68 million ha of agricultural land alone, is a major driver of soil erosion, increases flood frequency and reduces groundwater recharge. Agricultural soil compaction has been intensively studied, but there are no systematic studies investigating the extent of compaction in urban ecosystems, despite the repercussions for ecosystem function. Urban areas are the fastest growing land… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 18 publications
1
39
0
3
Order By: Relevance
“…This is a first approximation, assuming SRC is used to substitute natural gas in domestic heating, and is based on 10Á3 odt ha À1 year À1 SRC yield (Aylott et al 2010), rather than the 6 odt ha À1 year À1 value of Strohbach et al (2012). In Leicester, soil quality data (Edmondson et al 2011(Edmondson et al , 2012(Edmondson et al , 2014 justify the higher yield value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a first approximation, assuming SRC is used to substitute natural gas in domestic heating, and is based on 10Á3 odt ha À1 year À1 SRC yield (Aylott et al 2010), rather than the 6 odt ha À1 year À1 value of Strohbach et al (2012). In Leicester, soil quality data (Edmondson et al 2011(Edmondson et al , 2012(Edmondson et al , 2014 justify the higher yield value.…”
Section: Discussionmentioning
confidence: 99%
“…This is a conservative approach as citywide analysis of soil properties in Leicester found that in most greenspaces, the soil quality matches or exceeds that of agricultural land (Edmondson et al 2011(Edmondson et al , 2012(Edmondson et al , 2014. A series of spatial restriction criteria, based on UK Energy Crop Scheme guidance (Natural England 2013b) and findings of biofuels research (Renewable Fuels Agency 2008; Aylott et al 2010), was developed (Table S2) to identify suitable planting sites and the annual yield possible across the study area was calculated.…”
mentioning
confidence: 99%
“…It also provides a good estimate of soil compaction due to reduced total porosity. Compaction is generally associated with land degradation (the inverse of soil quality, Huber et al, 2008) and can result in decreases in water holding capacity, water infiltration, microbial functions and biogeochemical cycling (Edmondson et al, 2011;Gregory et al, 2015a). It is derived by measuring dry bulk density (BD) modified by clay content (C) and is a very useful parameter for spatial interpretations that require a measure of the compactive state of soils (Jones et al, 2003).…”
Section: Packing Densitymentioning
confidence: 99%
“…In all plots, duplicate soil cores were taken under annual vegetable crops and, where available, another duplicate set of samples were taken under woody fruit bushes or trees. Samples were taken from the topsoil layer in two depth increments (0-7 cm and 7-14 cm), using specialist corer that removes undisturbed soil samples for BD analysis (Edmondson et al 2011). Sample locations for soils in other urban greenspaces were generated in a GIS using two high spatial resolution data sets.…”
Section: S O I L S U R V E Ymentioning
confidence: 99%
“…Soils in urban greenspaces have recently been shown to make an important contribution to provision of ecosystem goods and services especially in holding large stocks of SOC (Pouyat, Yesilonis & Nowak 2006;Churkina, Brown & Keoleian 2010;Edmondson et al 2011Edmondson et al , 2012Edmondson et al , 2014. However, we currently know nothing about how soil management for own-growing in allotments impacts on the main soil quality indicators.…”
mentioning
confidence: 99%